Examination of question types used by elementary school teachers in the process of teaching and learning - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
This study was carried out on 156 elementary school teachers working in 20 elementary schools in 5 different districts of Istanbul. A total of 492 class hours were observed and the questions asked by teachers during these class hours were recorded on essay type observation forms. Percentages, frequency distributions and weighted mean values were calculated for the data obtained. The teachers were observed to ask a total of 4,467 questions, which were classified as open-ended and one-answer. The results showed that 85.60% of all the questions asked by the teachers were one-answer, while only the remaining 14.40% were open-ended. It was also found that teachers asked an average of 9.08 questions in one class hour in all courses. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Elementary school teacher; questions; type of questions; open-ended question; one answer question